Evaluation of Urban Rainwater Storage Sizing Based on Daily Meteorological Data for the 1901 – 2020 Period - Rácz, Tibor; Waltner, István; Gelybó, Györgyi (Journal of Central European Green Innovation, 2022)
The study presents the investigation of rainwater reservoirs for collecting roof water from buildings, with a roof size typical for Hungarian conditions and a possible water use. The study was based on a simple model based on daily precipitation and temperature data.The model results, which took into account 120 years of data, are suitable for showing the effects of the fluctuations that have taken place in the meantime as the spontaneous fluctuations of the climate and by climate change that can be traced back to human activity. In addition, it was possible to examine some of the characteristics of each reservoir with a nominal volume. In the study, we have presented the results of rainwater collection in the case of annual (whole-year) and seasonal (frost-free) periods. The examination of an extremely large reservoir was also the subject of the study, during which the change in the irrigated area was analyzed. One of the findings of the tests is that the estimated upper limit of the optimal size of the reservoir. It was found that with the frame of the recorded input and output parameters, taking into account the meteorological data, the maximum reasonable size of the tank is around 20 m3, although the optimal volume is to be found well below this value. The utilization of greater reservoir cannot be interpreted. We also examined how the ratio of individual parameters changed over the past century. The conclusion of the study is that water retention for irrigation purposes is definitely positive. The design of a larger reservoir usually results in better indicators, but it is possible to raise the question of how the return on investment costs can be validate in the case of a household. This question should be the subject of further investigations.